BERMAIN DAN BELAJAR: PROGRAM PENINGKATAN KETERAMPILAN SOSIAL ANAK SD MELALUI AKTIVITAS EDUKATIF - Kabanga, Theresyam; Tulak, Topanus; Allo Linggi, Lutma Ranta; Maharani, Yan; Bandangan Leke, Reformasi (Jurnal Abdimas Bina Bangsa, 2025)
The "Play and Learn" program is designed to enhance the social skills of elementary school children through enjoyable educational activities. Social skills, such as communication, teamwork, and emotional understanding, are essential aspects that need to be developed from an early age to support children's success in personal and academic life. This program adopts a participatory approach based on Bandura's social learning theory and Piaget's concept of "active learning," emphasizing the importance of direct interaction and active involvement of children in the learning process. The program implementation consists of three main stages: initial observation to understand children's needs, activity execution involving collaborative games and social simulations, and evaluation and monitoring to measure outcomes. The expected results of this program include improved communication skills, the establishment of a culture of teamwork in the school environment, and better understanding of self and others' emotions. This program offers an experiential-based solution to help children develop sustainable social skills while contributing to strengthening their emotional intelligence in the digital era. Broader implementation in various schools is expected to create a generation that is not only academically competent but also equipped with strong interpersonal skills